2006
DOI: 10.1103/physrevb.74.134420
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of the hyperfine interactions and spin dynamics inα-iron(II) phthalocyanine

Abstract: The 57Fe Mössbauer spectroscopy on ␣-iron͑II͒ phthalocyanine ͑FePc͒ as a function of temperature ͑1.3 Ͻ T Ͻ 295 K͒ and applied field ͑0 Ͻ B Ͻ 10 T͒ has been used to study the peculiar magnetic properties of this ferromagnetic quasilinear chain type compound. One sextet with an internal hyperfine field B int = 66.2 T was observed at 1.3 K, a very large value for a bivalent iron with S = 1 pointing to the existence of large positive orbital and dipolar contributions in the investigated FePc. Under an applied fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 51 publications
9
45
0
Order By: Relevance
“…This fact also explains the Mössbauer spectroscopy ͑MS͒ as a function of field measurements, which found the highest hyperfine field of positive sign ever measured on an Fe͑II͒ ion ͑B hf = 66.2 T͒. 19 Indeed, this requires the existence of a large orbital moment to explain the field dependence of the low temperature MS sextets, in excellent agreement with our result.…”
Section: X-ray Spectroscopy Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…This fact also explains the Mössbauer spectroscopy ͑MS͒ as a function of field measurements, which found the highest hyperfine field of positive sign ever measured on an Fe͑II͒ ion ͑B hf = 66.2 T͒. 19 Indeed, this requires the existence of a large orbital moment to explain the field dependence of the low temperature MS sextets, in excellent agreement with our result.…”
Section: X-ray Spectroscopy Resultssupporting
confidence: 79%
“…ground state configuration is 3 E, under lower symmetry than D 4h . They mention that this configuration confirms the 3 E proposed earlier from Mössbauer experiments, 19 or from theoretical density functional theory ͑DFT͒ calculations on the FePc isolated molecule. 17 In fact, the empty state configuration given in Ref.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…(There is, however, general consensus that the ground state has S=1.) Meanwhile, recent Mössbauer spectroscopy and X-ray magnetic circular dichroism (XMCD) experiments 8,9 for α-FePc found a 3 E g ground state with a large orbital moment of 0.53 µ B , and a large hyperfine field of 66.2 T that is parallel to the magnetic moment 8 . Magnetization hysteresis experiments, furthermore, indicated that the easy axis of magnetization is parallel to the molecule plane, i.e., a planar magnetic anisotropy 9 .…”
Section: Structure Of Fe-phthalocyaninementioning
confidence: 99%